Museums, international exhibitions and China's cultural diplomacy - Kong, Da (Lecturer in museum studies) (London ; New York, NY : Routledge/Taylor & Francis Group, 2021)
"Museums, International Exhibitions and China's Cultural Diplomacy examines the role museums and, more specifically, international exhibitions, have played in shaping China's international image to date. Drawing on theories and methods from museum studies and international relations, the book evaluates the contribution international exhibitions make to China's cultural diplomacy strategy. Considering their impact on the country's international image, Kong also probes the mechanisms and processes involved, examining in detail the policy of, and international activities promoted by, the Chinese government. The book also analyses the motives of the Chinese and overseas museums that host these exhibitions. Taking some major exhibitions that were on show in the UK during the 21st century as a representative case study, the book reveals the mechanisms by which these exhibitions were developed and shared overseas. Questioning who really shapes the image of China, Kong challenges Western assumptions and looks ahead to consider whether, moving forward, the Chinese government and museums could work together in a mutually beneficial way. Museums, International Exhibitions and China's Cultural Diplomacy contributes to the growing literature on museums and diplomacy. As such, it will be of interest to academics and students engaged in the study of museums and heritage, international relations, culture, politics, China and wider Asia"--
China's cultural diplomacy in image building -- Museums and international exhibitions as instruments of China's cultural diplomacy -- International exhibitions as China's cultural diplomacy toward the UK -- International exhibitions and the image of China -- International exhibitions and a contemporary China -- Who shapes the image of China?
OCLC-licensed vendor bibliographic record.
Keywords: Cultural diplomacy -- China; Museum exhibits -- Political aspects -- China; Public opinion -- Great Britain -- Case studies; China -- Foreign public opinion; China -- Foreign relations -- 21st century; China -- Public opinion, British -- Case studies